Point-of-Care Tests for Bladder Cancer: The Influencing Role of Hematuria. (22nd November 2011) - Hennenlotter, Joerg; Huber, Severine; Todenhöfer, Tilman; Kuehs, Ursula; Schilling, David; Aufderklamm, Stefan; Gakis, Georgios; Schwentner, Christian; Stenzl, Arnulf
Abstract : Introduction . Several point-of-care tests (POCT) are available for the diagnosis of bladder cancer (BC). We evaluate the impact of HU (hematuria) on performance of POCTs. Materials and Methods . Urine from 10 donors was diluted with blood from 0.5 to 0.00625%. BladderCheck R, BTAstat R, BCM R, and BTA R tests were applied. Tests were additionally conducted in 54 patients with HU. HU was stratified according to the amount of erythrocytes (RBC)/ μ L using two systems: (1) no HU; mild microscopic HU; severe microscopic HU; gross HU; (2) I <25 RBCs; <250 II; ≥250 III. Results were compared to HU status and histopathology. Results . Gross HU became evident between 2090 RBCs/ μ L and 1065/ μ L. Addition of blood led to default tests in all 4: BladderCheck R 0.25%; BCM 0.025%, BioNexia 0.00625%, and BTAstat <0.00625%. Rates of false positives for BladderCheck, BTAstat, BCM, and BioNexia were 5.9, 11.8, 0, and 1.8% without HU and 0, 66.7, 44.4, and 66.7% with HU. BTAstat, BCM, and BioNexia were independently influenced by HU (P < 0.0002 ). Conclusions . NMP22-BladderCheck was most resistant to blood. The diagnostic yield of all others was significantly influenced by HU. A well-defined HU grading helps to define limits of HU for a reliable interpretation of BC-POCTs.